A stakeholder perspective on public sector innovation: why position matters - de Vries, Hanna; Tummers, Lars; Bekkers, Victor (International review of administrative sciences, 2018)
Studies on the adoption of innovations often treat an organization as a uniform entity. Such studies implicitly assume that perceptions regarding the adoption of an innovation are identical across the organization. However, organizational theory and change management literature argue that organizations are composed of distinct groups that have different values and goals. It is therefore important to dissect the organization and to look at the various internal stakeholders involved. In this study, we follow this advice and study how two key organizational groups (city managers and Works Council members) perceive their organization’s members’ views regarding the specific innovation of teleworking. We use unique data collected through two nationwide surveys of city managers and Works Council members. The results show that there are crucial differences in the perceptions of the two groups, with city managers generally being more positive about the innovation. Based on our analysis, we conclude that it is important to distinguish between different organizational stakeholders in the innovation adoption process and that managers should be aware of a bias in their perceptions. Points for practitioners It is important to distinguish between the various organizational stakeholders in the innovation adoption process because they probably have different attitudes regarding an innovation. Managers should look beyond their own perceptions regarding an innovation and be aware that they are probably more positive in their perceptions than are others in their organization. More specifically, we found that Works Council members attach more importance to the ability to try out innovations before their full introduction than city managers. It is also more important for them that an innovation seems easy to implement and use.